Studi Komparatif Daya Saing Ekspor CPO dan Karet di Provinsi Jambi dalam Periode 2000-2016 - Deby Anggun Sari (Fakultas Hukum dan Ekonomi Bisnis, 2021)
Commodity export competitiveness is one of the indicators used to measure progress of the country's economy. This study aims to analyze the development, calculate how large the competitiveness and to analyze the factors that influence the competitiveness of exports of CPO and rubber in Jambi province in the period 2000-2016.dengan using the Revealed Comparative Advantage (RCA), data used secondary data from BPS, Bank Indonesia Disperindag and Jambi provinces. in this study using two analysis is descriptive analysis and quantitative analysis, analytical method used is multiple linear regression using the program help eviews9. The results of this study indicate that commodity CPO and rubber products have high competitiveness for export. The factors affecting the competitiveness of CPO and rubber products are export prices, exchange rates, and labor. Based on the regression results found that the independent variables are price and exchange rate significant effect on the dependent variable, namely RCA exports of CPO and rubber with each R2 of 59.22 percent in oil palm (CPO) while the remaining 40.78 percent is influenced by variables another, in the rubber commodity amounted to 57.53 while the remaining 42.47 percent is influenced by other variables notsincluded in this study.